Construcción de promotores trampa basados en efectores TAL de Xanthomonas axonopodis pv. manihotis (2020)
Cassava bacterial blight caused by Xanthomonas axonopodis pv. manihotis (Xam), is the main bacterial disease that affects Cassava crops. Xam virulence has been attributed to TALEs (Transcription Activator-Like Effectors), that bind to promoter elements of the host target genes to induce their expression. The TALome characterization of diverse Colombian strains of Xam have led to the identification of TAL14, TAL20, and TAL22 as the most recurrent TAL effectors in the pathogen populations in the country. With the purpose to develop a biotechnological tool for producing broad-spectrum resistance against Xam, this study generated a genetic construction of a trap promotor containing EBEs (Effector Binding Elements) for TALEs 14, 20 and 22. The EBE sequences were inserted in the minimal Bs3 promoter (pBs3min) using site-directed mutagenesis, to construct the TriEBE promoter EBETAL14Xam and EBETAL22Xam were cloned flanking EBETAL20Xam. The reporter gene GUSplus and 35s terminator were inserted flanking the promoters, the resulting vectors were used to transform Agrobacterium tumefaciens and perform the functional evaluation in Nicotiana tabacum. Finally, the promoters activation was evidenced because of TAL14 and TAL20 presence in co-infiltrated leaves. These results suggest that trap promoters developed in the present research can be activated by any Xam strain with TAL14 or TAL20 in its TALome, therefore representing a novel recognition cassette for most strains of the pathogen in Colombia.